La Riga. - Oborenko, Santa; Traumane, Mara; Exhibition. La Riga. Fabbrica del Vapore Milano. 2003-02-10. 2003-03-04 (Milano : C/O careof & Viafarini Milano Fabbrica del Vapore Milano.)
Oborenko, Santa ; Korps, Girts ; Salmanis, Kriss ; Virbulis, Martins ; Dzerina, Dace ; Rubeze, Ieva ; Marcinkevica, Liga ; Neiburga, Katrina ; Broks, Ervins ; Ziders, Felikss ; Ratniks, Martins ; Podnieks, Kaspars ; Kursisa, Kristine ; Mitrevics, Miks
biog., tent. [1 p.]
Engels
Italiaans
boek